2008
DOI: 10.1242/jeb.022160
|View full text |Cite
|
Sign up to set email alerts
|

A microarray-based transcriptomic time-course of hyper- and hypo-osmotic stress signaling events in the euryhaline fishGillichthys mirabilis:osmosensors to effectors

Abstract: SUMMARYCells respond to changes in osmolality with compensatory adaptations that re-establish ion homeostasis and repair disturbed aspects of cell structure and function. These physiological processes are highly complex, and require the coordinated activities of osmosensing, signal transducing and effector molecules. Although the critical role of effector proteins such as Na -co-transporters during osmotic stress are well established, comparatively little information is available regarding the identity or expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
117
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(125 citation statements)
references
References 91 publications
8
117
0
Order By: Relevance
“…Comparatively little is known about the mechanisms comprising the immediate-early responses of cells to osmotic stress relative to the mechanisms of downstream effectors of osmotic acclimation (43,44). However, immediate-early transcriptional responses are highly correlated with the pattern of population variation in transcriptional trajectories during acclimation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Comparatively little is known about the mechanisms comprising the immediate-early responses of cells to osmotic stress relative to the mechanisms of downstream effectors of osmotic acclimation (43,44). However, immediate-early transcriptional responses are highly correlated with the pattern of population variation in transcriptional trajectories during acclimation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The MIB pathway utilizes two enzymes, myo-inositol phosphate synthase (MIPS) and inositol monophosphatase (IMPA), to generate myo-inositol endogenously from glucose-6-phosphate (G-6-P) in a two-step reaction (Geiger and Jin, 2006). The study by Fiol et al (Fiol et al, 2006b) was the first to identify upregulation of MIPS mRNA in response to acute hyperosmotic challenge in tilapia gill, and since then, several studies have confirmed induction of the MIB pathway in other euryhaline species exposed to salinity challenge (Evans and Somero, 2008;Kalujnaia et al, 2009;Kalujnaia et al, 2010;Kalujnaia et al, 2013). In mammals, IMPA has at least two isoforms, originating from different genes (Ohnishi et al, 2007;Shamir et al, 2001), while MIPS can have alternative splice variants (Seelan et al, 2009) derived from the same gene.…”
Section: Introductionmentioning
confidence: 99%
“…Induction of these two genes is also evident in other euryhaline fish exposed to acute salinity stress. For instance, elevated salinity increases MIPS abundance in O. niloticus and Anguilla anguilla (52) and IMPA1.1 abundance in Gillichthys mirabilis and A. anguilla (53)(54)(55)(56). The MIB pathway promotes the accumulation of high concentrations of the compatible osmolyte myo-inositol, which protects cells from salinity-induced damage (44,48,57).…”
Section: Discussionmentioning
confidence: 99%